2016
DOI: 10.1080/13675567.2015.1115471
|View full text |Cite
|
Sign up to set email alerts
|

Reverse logistics capabilities and firm performance: the mediating role of business strategy

Abstract: This study aims to examine the impact of reverse logistics capabilities on firm performance and mediating role logistics strategies. We reviewed three theories of reverse logistics capabilities: (a) Resource-based view of the firm, (b) Transaction cost economics, and (c) Institutional theory. We examined six reverse logistics capabilities: Logistics information management, close-loop capability, supply chain integration, supply chain coordination, conformity capability, and institutional incentives. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 70 publications
0
68
0
5
Order By: Relevance
“…Excellence in logistics practices are strongly related to high‐quality business performance. According to Vlachos (2016), reserve logistics activities and capabilities have a direct impact on a firm's performance. Performance measures that indicate the influence of green practices on company performance need to be further investigated (Pinto, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Excellence in logistics practices are strongly related to high‐quality business performance. According to Vlachos (2016), reserve logistics activities and capabilities have a direct impact on a firm's performance. Performance measures that indicate the influence of green practices on company performance need to be further investigated (Pinto, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, several studies have shown that logistics IS improves economic performance [32,66], along with operational performance [45,57,66], and strategic performance [36]. However, a survey [35] conducted on the mobile phone industry in China revealed a lack of relationship between logistics IS and RL performance, indicating that even CLSC-focused IS is not the whole story.…”
Section: Value Creation Factorsmentioning
confidence: 99%
“…Green supply chain management (GSCM) is a new and evolving area of supply chain management. The GSCM has a number of areas that including internal and external management (Chan et al, 2012), green procurement (Chien & Shih, 2007), green retailing (Dabija & Pop, 2013;Dabija et al, 2018), environmental orientation (Chan et al, 2012), sustainability (Popp et al, 2018;Oláh et al, 2019) and return logistics (Vlachos, 2016;Slusarczyk & Kot 2018;Kot et al, 2018).…”
Section: Environment Friendly Practicesmentioning
confidence: 99%